Sustaining the Unresolvable: Micro-Pain and the Ontology of Heterogeneity - Wang, Xiaole (Taideyliopiston Teatterikorkeakoulu, 2025)
This thesis investigates micro-pain as repetitive, low-intensity, often unconscious bodily discomfort, as an ontologically significant phenomenon. Rather than responding to micro-pain as a symptom to be given or eliminated, as is common in psychological or medical discourse, this research uses an interdisciplinary framework that brings phenomenology, philosophical theory, and performance art into coalition. Drawing on Merleau-Ponty's body schema, examining how micro-pain as a disturbance of body schema that disrupts bodily transparency and brings the body into perceptual presence. But not all micro-pain can be reintegrated into functional coordination. Certain forms persist, repeat and resist resolution, revealing themselves not as temporary disruptions but as persistent residues. In an attempt to describe this remainder that cannot be reduced, the framework shifts on Georges Bataille's expenditure and heterogeneity theory to conceptualize micro-pain as a residual form of sensation that resists utility, regulation, and symbolic integration. This thesis is not intended to cure or solve micro-pain. Instead, it proposes that certain kinds of pain persist not as dysfunction but as structural residue. Through an analysis of my own practice, I illustrate how micro-pain is made habitual embodied through repetition, residue, and non-teleological gesture. In this context, the body is one in which consumption, discomfort, and ritual intersect. The gesture is non-expressive and non-productive, but sustains pain as a continuous condition. By refusing to treat micro-pain as either metaphor or pathology, this thesis proposes an alternative model in which it is approached as a mode of being. Micro-pain disrupts the foundations of corporeal coherence and discloses the limits of normalization. Rather than asking how such pain could be resolved, this research investigates what its non-functional and unresolved presence tells us about the structure of sensation and the weight of being.
Keywords: Micro-pain; Expenditure; Ontology; Body schema; Heterogeneity; Performance art; Bataille, Georges; ontologia (filosofia); somatestesia; heterogeenisuus; performanssi; LAPS